THE INFLUENCE OF PERCEIVED PRICE AND E-SERVICE QUALITY ON CUSTOMER SATISFACTION AND THEIR IMPACT ON CUSTOMER LOYALTY IN USING GO-JEK SERVICES IN DKI JAKARTA PROVINCE - Suharni Rahayu; Nandan Limakrisna; Jan Horas V. Purba (International Journal of Economy, Education and Entrepreneurship, 2023)
This study aims to analyze and prove the effect of perceived price and e-service quality on customer satisfaction and their impact on customer loyalty in using Go-Jek services in DKI Jakarta Province. This research method uses the causality method. The population of this research is Go-Jek customers in DKI Jakarta while the number of samples used is 200 respondents. The data analysis method used in this study is SEM-PLS. This study resulted in the following conclusions: Price Perception has a positive and significant influence on Go-Jek Customer Satisfaction in DKI Jakarta Province. E-Service Quality has a positive and significant influence on Go-jek Customer Satisfaction in DKI Jakarta Province. Simultaneously Perceived Price and E-Service Quality have a positive and significant influence on Go-jek Customer Satisfaction in DKI Jakarta Province. Price Perception has a positive and significant influence on Go-jek Customer Loyalty in DKI Jakarta Province. E-Service Quality has a positive and significant influence on Go-jek Customer Loyalty in DKI Jakarta Province. Customer Satisfaction has a positive and significant influence on Go-jek Customer Loyalty in DKI Jakarta Province. Simultaneously Perceived Price, E-Service Quality, and Customer Satisfaction have a positive and significant influence on Go-jek Customer Loyalty in DKI Jakarta Province. Perceived Price has a positive and significant influence on Customer Loyalty through Go-Jek Customer Satisfaction in DKI Jakarta Province. E-Service Quality has a positive and significant influence on Customer Loyalty through Go-jek Customer Satisfaction in DKI Jakarta Province. Therefore, the variable of customer satisfaction is a full mediating variable